2012
DOI: 10.2306/scienceasia1513-1874.2012.38.175
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and strength of blended FBC-PCC fly ash geopolymer containing gypsum as an additive

Abstract: This study focused on the microstructure and strength of blended fluidized bed coal combustion fly ash (FBC-FA) and pulverized coal combustion fly ash (PCC-FA) geopolymers containing gypsum as an additive. The source materials consisted of 100% FBC-FA and a blend of 75% FBC-FA and 25% PCC-FA. Gypsum was used as an additive at the dosage levels of 0, 5, and 10%wt of the source materials. NaOH and Na 2 SiO 3 were used to activate aluminosilicate sources and temperature curing to accelerate the geopolymer reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…The 2% replacement resulted in the best strength result, observed at 28 days (see Figure 1); however, the higher replacement ratios, more than 4%, markedly lowered the overall strength. Similar trends were observed in earlier studies that investigated the influence of gypsum with a range of replacement ratios for fly ash activated with NaOH and Na-silicate [4,8,13,14]. Those studies reported that the strengths of fly ash geopolymers increased up to a certain point of gypsum addition (~1% to 10%) and decreased above that addition; however, no detailed discussion concerning the causes of the strength decrease was made.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…The 2% replacement resulted in the best strength result, observed at 28 days (see Figure 1); however, the higher replacement ratios, more than 4%, markedly lowered the overall strength. Similar trends were observed in earlier studies that investigated the influence of gypsum with a range of replacement ratios for fly ash activated with NaOH and Na-silicate [4,8,13,14]. Those studies reported that the strengths of fly ash geopolymers increased up to a certain point of gypsum addition (~1% to 10%) and decreased above that addition; however, no detailed discussion concerning the causes of the strength decrease was made.…”
Section: Resultssupporting
confidence: 80%
“…Note that sample F-NW was made within a typical range of successful synthesizing conditions of activator and curing temperature for fly ash geopolymer, as reported in the literature [3,4,6,8,14,18]. Nonetheless, although the F-NW sample showed a high increasing rate of strength gain over 30 MPa/day at one day and reached its highest value (44.74 MPa) after seven days, the sample deteriorated to half of the seven-day strength value by 28 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations